Directions and Characteristics of Turkey's Regional Foreign Policy (International relations and international law Journal, 2023)
One of the characteristic features of today's multipolar world system is the lack of long-term foreign policy analysis. This is largely due to the fact that the actors in the current global system are multilateral and the course of events cannot be fully shaped in their favour. However, the real reason is that 'change' and 'transformation' are two of the most fundamental concepts of twentieth century world politics. Moreover, it is no coincidence that these two concepts are the ones most frequently used in introductions to post-2000 foreign policy analysis. This new situation concerns small and medium-sized or underdeveloped and developing countries as well as developed and great powers. Therefore, foreign policy analysis needs to be reviewed frequently. Located in the Middle East, one of the most unstable and tense regions of the world, Turkey inevitably has to be constantly involved in global and regional changing situations. Due to this necessity, Turkish foreign policy has entered a phase of rapid change/transformation. This article assesses the new directions and features of Turkey's foreign policy and its implications. In this context, the motives of Turkey's foreign policy, especially in the Middle East and Turkic world in the new world order that is emerging as a result of the Russian-Ukrainian war and what role was/is given to Turkey in this process of change will be examined. To this end, after identifying the main parameters that shaped this period, the policies pursued in the Middle East and the Turkic World will be assessed. The choice of Middle East and Turkic World as the field of application in this paper is related to Turkey's geopolitical, economic, strategic position in the region and its common historical and cultural memory with the countries in the region. In the following, the basic principles of Turkey's foreign policy will be examined and then the implementation of these principles in the Middle East and Turkic world will be analysed.Key words: Turkic world, Middle East, geopolitics, Turkish foreign policy, hegemony.